Anti-necrotic and cardioprotective effects of a cytosolic renin isoform under ischemia-related conditions - Wanka, Heike; Hoffmann, Sigrid (Journal of molecular medicine, 2016)
In the heart, secretory renin promotes hypertrophy, apoptosis, necrosis, fibrosis, and cardiac failure through angiotensin generation from angiotensinogen. Thus, inhibitors of the renin-angiotensin system are among the most potent drugs in the treatment of cardiac failure. Renin transcripts have been identified encoding a renin isoform with unknown targets and unknown functions that are localized to the cytosol and mitochondria. We hypothesize that this isoform, in contrast to secretory renin, exerts cardioprotective effects in an angiotensin-independent manner. Cells overexpressing cytosolic renin were generated by transfection or obtained from CX(exon2-9)renin transgenic rats. Overexpression of cytosolic renin reduced the rate of necrosis in H9c2 cardiomyoblasts and in primary cardiomyocytes after glucose depletion. These effects were not mediated by angiotensin generation since an inhibitor of renin activity did not influence the in vitro effects. siRNA-mediated knockdown of endogenous cytosolic renin increased the rate of necrosis and aggravated the pro-necrotic effects of glucose depletion. Isolated perfused hearts obtained from transgenic rats overexpressing cytosolic renin exhibited a 50 % reduction of infarct size after ischemia-reperfusion injury. Cytosolic renin is essential for survival, both under basal conditions and during glucose starvation. The protective effects are angiotensin-independent and contrary to the known actions of secretory renin.Key messages A cytosolic isoform of renin with unknown functions is expressed in the heart. Cytosolic renin diminishes ischemia induced damage to the heart. The protective effects of cytosolic renin contradict the known function of secretory renin. The effects of cytosolic renin are not mediated via angiotensin generation. Renin-binding protein is a potential target for cytosolic renin.
Gesehen am 23.01.2019
Published online: 11 August 2015